Pengembangan Media Pembelajaran Flipbook Pengelasan untuk Siswa SMK IPT Semarang - Cokro, Sulistio; Iskandar, Ranu (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to develop flipbook-based digital learning media on SMAW and GMAW welding materials for SMK IPT Semarang students. The method used is Research and Development (R&D) with reference to the Plomp and Luther development model. The instruments used in this study include validation sheets, learning outcome tests, and student response questionnaires. The validation results show that the media is declared valid with a score of 75% from media experts, and 80% from material experts. This flipbook is considered effective in increasing learning motivation and understanding of welding concepts, and is in accordance with the characteristics of generation Z students. In addition, this media also makes it easier for teachers to deliver material interactively. Therefore, flipbook welding learning media is worthy of being an innovative alternative in the vocational learning process in SMK.